Relationship between ventricular repolarization parameters and the inducibility of ventricular arrhythmias during electrophysiological study in patients with coronary artery disease - Carvalho,Guilherme Dagostin de (2022)
SUMMARY OBJECTIVE: Risk stratification of sudden cardiac death in patients with coronary artery disease is of great importance. We evaluated the association between ventricular repolarization and induction of malignant ventricular arrhythmias on electrophysiological study of patients with coronary artery disease. METHODS AND RESULTS: A total of 177 patients (65±10.1 years, 83.6% male, mean left ventricular ejection fraction [LVEF] 37.5±13.6%) were analyzed. For each 10 ms increment in the QT interval, there was a 7% increase in malignant ventricular arrhythmias inducibility; QT cutoff point of 452 ms had an accuracy of 0.611 for predicting malignant ventricular arrhythmias (p=0.011). Male gender (odds ratio [OR]=4.18, p=0.012), LVEF <35% (OR=2.32, p=0.013), amiodarone use (OR=2.01, p=0.038), and prolonged QT (OR=1.07, p=0.023) were associated with malignant ventricular arrhythmias. In patients with ventricular dysfunction, QT >452 ms was associated with significantly increased risk of malignant ventricular arrhythmias (OR=5.44, p=0.0004). In those with LVEF ³35%, QT dispersion (QTd) was significantly higher in patients with inducible malignant ventricular arrhythmias. QTd >20 ms had 0.638 accuracy and 81.3% negative predictive value in predicting malignant ventricular arrhythmias. CONCLUSION: QT interval is an independent factor associated with malignant ventricular arrhythmias in patients with coronary artery disease. The combination of ventricular dysfunction and prolonged QT interval is associated with a 5.44-fold increase of malignant ventricular arrhythmias induction. Male gender, amiodarone use, and decreased left ventricular ejection fraction are also associated with increased risk of inducibility of malignant ventricular arrhythmias on the electrophysiological study.